ANALYSIS OF THE IMPLEMENTATION OF THE ASSIMILATION AND EDUCATION FACILITIES PROGRAM IN AN EFFORT TO IMPROVE THE SKILLS OF PRISONERS IN CLASS IIB KAYU AGUNG PRISON - Damara, Muhammad Donny; Warih, Wido Cepaka (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to analyze the implementation of the Sarana Assimilasi dan Edukasi (SAE) Program in an effort to improve the skills of prisoners at Class IIB Kayu Agung Correctional Facility. Using qualitative research methods, this study explores the various obstacles faced in implementing the program, focusing on aspects of policy standards, resources, inter-organizational communication, characteristics of implementing agents, economic, social, and political conditions, and attitudes of policy implementers. The results show that there are significant obstacles such as inadequate facilities, lack of trained human resources, and ineffective communication between implementers and prisoners. In addition, unsupportive economic and social conditions as well as less motivating attitudes of implementers also affect the effectiveness of the program. This research is expected to provide insights for the improvement of policies and practices in the implementation of prisoner development programs. Keywords: Assimilation and Education Facilities (SAE) Program; Skills; Prisoners